Determinants of behaviour of working capital requirements of BSE listed companies: An empirical study using co-integration techniques and generalised method of moments - Rakesh Kumar Sharma; Apurva Bakshi; Sheena Chhabra (Cogent Economics & Finance, 2020)
The paper investigates the determinants of working capital to forecast the future requirement of working capital of BSE-listed top 150 companies in India. The study is conducted by collecting the data of 150 top-performing BSE listed companies for the time period of 2009-2017. The ten firm-level explanatory variables and one dummy variable to characterize the nature of business i.e. manufacturing and service sector companies are used to discover the significant determinants of gross and net working capital of selected companies. The four alternative methods are used to verify and validate the results obtained from each other viz. Ordinary Least Square (OLS), fully modified OLS (FMOLS), dynamic OLS (DOLS) and generalized methods of moments (GMM). The empirical findings of four different methods indicate that tangibility, leverage, nature of business and board size are observed as significant factors to forecast the future requirements of net working capital. Return on common equity (ROCE), board size; indicate the positive association with gross working capital. On the other hand, tangibility, nature of business and size of the firm show a negative relationship with gross working capital requirements. The findings from different methods have resulted in similar significant determinants to predict the future requirement of the net and gross working capital. The outcome of the study will be useful for management authorities for maintaining the optimum level of working capital and to forecast future requirements of working capital.
Keywords: M40; G30; G31; G32; 330; networking capital; gross working capital; net tangible; leverage; asymmetric information; sargan test; generalised method of moment; dynamic OLS; fully modified OLS